Analysis of Robotic Vision by Using Image Processing Trying to Find the Shortest Path to Goal Using Voronoi Diagram - Noori, Amani Y; Majeed, Suhad F (Al-Nahrain Journal of Science, 2017)
In this paper we present a method to navigate a mobile robot for finding the path to his goal. This method determines the shortest path for robot to transverse to its target location while detecting and avoiding obstacles of different shapes in indoor environment. The vision of robot is first captured as an image using laptop cam, the image analysis is based on image processing in Matlab to identify the existence of obstacles within the environment. Voronoi diagrams (VDS) is a roadmap method that provides all possible paths in an environment containing stationary obstacles. By using a distance formula we get the shortest path for robot among three paths. The program is written in Matlab 2010 with image processing toolbox, the proposed technique does not make use of any other type of sensor other than laptop cam.